The joint impact of technology innovation and tourist arrivals on Japan’s economic growth - Luah, Cheryl Jing Ning; Ang, Ee Zhern; Chong, Poh Fang; Teoh, Yee Che; Wan, Wai Kit (2019)
Japan is a vulnerable country to natural disaster and this is a significant issue as it diminishes the confidence level of tourists toward Japan. The aim of this research is to examine the joint impact of technology innovation and tourist arrivals on Japan’s economic growth. By using time series data ranging from 1986 to 2016, we applied autoregressive distributed lag (ARDL) model to test the relationship between dependent variable, economic growth and independent variables namely technology innovation, tourist arrivals, labor, capital and an interaction term between technology innovation and tourist arrivals. The results of our study showed that there is long run positive relationship between technology innovation, tourist arrivals, capital and Japan’s economic growth respectively. Meanwhile, there is long run negative relationship between labor and Japan’s economic growth. The joint impact effect for the interaction term between technology innovation and tourist arrivals is substitute effect. Therefore, Japan government could focus on policies to promote R&D innovation to reduce the risks and consequences resulting from natural disaster in order to boost the confidence level of tourists toward Japan and this could lead to economic growth.